Extending the dialogue : interactional and multimodal strategies in synchronous mobile mathematics tutoring on MXit - Robbins, Bonita (School of Education, 2015)
The aim of this study was to explore the interaction between learners and tutors in Dr Math, a mathematics tutoring project that uses instant messaging and the mobile application, MXit. There is currently little computer-mediated communication research available about the uses of mobile instant messaging for mathematics tutoring. This study utilizes the Exchange Structure Analysis model (ESA), adopted from Lim (2006) to explore tutoring interactions between Dr Math learners and tutors over a short period. A quantitative analysis of turn-taking in tutoring interactions during February is used to identify the characteristic roles of tutors and learners; their strategies for controlling and directing dialogue; and the kinds of pragmatic moves that are used during the scaffolding of mathematics learning, as revealed by the Dr Math log for the month of February, 2010. The log consisted of N= 6084 turns in interactions between 190 learners, who interacted with three different tutors.